On the Use of Wine amongst the Lower Orders in Scotland in the Seventeenth Century (Proceedings of the Society of Antiquaries of Scotland, 1858)
Joseph Robertson presents his argument that wine was a common drink in Scotland. As evidence, he quotes legislation from the seventeenth century prohibiting the sale and consumption of wine in the Western Isles.